Fossils Reveal Long-Term Continuous and Parallel Innovation in the Sacro-Caudo-Pelvic Complex of the Highly Aquatic Pipid Frogs - Gómez, Raúl O.; Pérez-Ben, Celeste M. (Frontiers in Earth Science, 2019)
Within the already peculiar Bauplan of anurans, pipid frogs have evolved an array of bizarre features that are commonly linked to their highly aquatic lifestyle. Among the latter, there are several distinctive sacro-caudo-pelvic features shared by extant pipids, which have been regarded as evolutionary novelties taking part of a specialized fore-aft-sliding ilio-sacral joint. Pipids and their kin (pipimorphs) have a rich fossil record documenting 130 million years of uninterrupted evolution in aquatic environments, which, along with our current understanding of their phylogeny and recently available musculoskeletal data, allows us to inquire on the patterns and processes that have led to their distinctive sacro-caudo-pelvic system with a deep-time perspective. Here, we take a phylomorphospace approach based on discrete character matrices and a scaffold tree derived from recent studies, making comparisons of morphospace occupation between pipids and other anurans, and morphospace occupation, disparity, levels of homoplasy, and shared evolving characters between different groups and/or over time across pipimorphs. In doing so, we focus on trends of morphological diversification and discuss the potential role that ecological and developmental constraints might have had in driving the evolution of the sacro-caudo-pelvic complex of pipid frogs. Our main findings reveal a pattern of continuous and parallel innovation early in the history of pipids followed by arrested evolution of novel morphologies towards the Recent. The latter, in turn, is mirrored by rampant homoplasy in the ilio-sacral sliding joint among extant pipid frogs. This study highlights the importance of fossils in revealing macroevolutionary patterns that will be otherwise veiled based on neontological data alone.